2022
DOI: 10.1007/s00018-022-04126-3
|View full text |Cite
|
Sign up to set email alerts
|

Citrullination in the pathology of inflammatory and autoimmune disorders: recent advances and future perspectives

Abstract: Numerous post-translational modifications (PTMs) govern the collective metabolism of a cell through altering the structure and functions of proteins. The action of the most prevalent PTMs, encompassing phosphorylation, methylation, acylations, ubiquitination and glycosylation is well documented. A less explored protein PTM, conversion of peptidylarginine to citrulline, is the subject of this review. The process of citrullination is catalysed by peptidylarginine deiminases (PADs), a family of conserved enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 185 publications
(237 reference statements)
0
44
0
Order By: Relevance
“…Citrullination is a post-translational modification by which arginine is converted to citrulline by peptidylarginine deiminases (PADs) unveiling novel antigenic epitopes that are over-enriched in several autoimmune diseases 55 . For the study of citrullinated targets, we pooled PF samples from EM+ patients based on their levels of anti-p53 AAb into two anti-p53 AAb groups (p53 high and p53 low ) ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Citrullination is a post-translational modification by which arginine is converted to citrulline by peptidylarginine deiminases (PADs) unveiling novel antigenic epitopes that are over-enriched in several autoimmune diseases 55 . For the study of citrullinated targets, we pooled PF samples from EM+ patients based on their levels of anti-p53 AAb into two anti-p53 AAb groups (p53 high and p53 low ) ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that women with endometriosis have native and citrullinated anti-p53 AAbs, among others. To date, five human PAD isotypes that are responsible for enzymatically modifying arginine to citrulline have been described 55 . PAD1 is expressed mainly in the uterus, PAD2 have widespread distribution including expression in the uterus, PAD3 is found in the epidermis, PAD4 expression is mainly restricted to leukocytes and PAD6 is expressed in ovaries and is a crucial enzyme in fertility 40,41,90,91 .…”
Section: Endometriosis Is Epidemiologically Linked To Autoimmune Dise...mentioning
confidence: 99%
“… 25 − 27 Further, new evidence suggests that citrullination can play a significant role in regulating gene expression and cellular metabolism. 28 Though citrullination was not reported earlier in Leptospira , 5667 deamidations of asparagine and glutamine as dynamic modifications are available in the supplementary files of the proteomic analysis work on Leptospira biflexa . 14 Another PTM associated to a greater degree with the aqueous fraction was acetylation, which is higher in aqueous.…”
Section: Discussionmentioning
confidence: 99%
“…NETosis constitutes a fast and effective response to infection, however, the deregulation of this process and associated release of inflammatory cytokines, proteases and active PADIs to the extracellular space, are highly destructive for the surrounding tissue and have been associated with the exacerbation of a remarkable array of pathologies, including RA, lupus erythematosus, ulcerative colitis, inflammatory bowel disease, atherosclerosis, sepsis, type I diabetes and severe Covid-19 (reviewed recently in detail in [ 125 ]) ( figure 2 ).…”
Section: Citrullination In Health and Disease —The Virtue A...mentioning
confidence: 99%